The Association of Conflict-Related Trauma with Markers of Mental Health Among Syrian Refugee Women: The Role of Social Support and Post-Traumatic Growth - Kheirallah KA; Al-Zureikat SH; Al-Mistarehi AH; Alsulaiman JW; AlQudah M; Khassawneh AH; Lorettu L; Bellizzi S; Mzayek F; Elbarazi I; Serlin IA (Dove Medical Press, 2022)
Khalid A Kheirallah,1 Sarah H Al-Zureikat,1 Abdel-Hameed Al-Mistarehi,1 Jomana W Alsulaiman,2 Mohammad AlQudah,1 Adi H Khassawneh,1 Liliana Lorettu,3 Saverio Bellizzi,4 Fawaz Mzayek,5 Iffat Elbarazi,6 Ilene A Serlin7 1Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Faculty of Medicine, Yarmouk University, Irbid, Jordan; 3Psychiatric Clinic, University of Sassari, Sassari, Italy; 4World Health Organization (WHO), Jordan Country Office, Amman, Jordan; 5School of Public Health, The University of Memphis, Memphis, TN, USA; 6Institute of Public Health, College of Medicine and Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates; 7International Institute for Advanced Training in Dance Movement Therapy, San Francisco, CA, USACorrespondence: Khalid A Kheirallah, Department of Public Health, Community Medicine, and Family Medicine, Medical School of Jordan University of Science and Technology, P.O. Box: 3030, Irbid, 22110, Jordan, Tel +962 7 9611 9094, Email kakheirallah@just.edu.jo Abdel-Hameed Al-Mistarehi, Department of Public Health, Community Medicine, and Family Medicine, Faculty of Medicine, Jordan University of Science and Technology, P.O.Box: 630001, Irbid, 22110, Jordan, Tel +962 7 9828 4360, Email awalmistarehi18@med.just.edu.joBackground: Syrian refugee women not only suffered the refuging journey but also faced the burden of being the heads of their households in a new community. We aimed to investigate the mental health status, traumatic history, social support, and post-traumatic growth (PTG) of Syrian refugee women.Methods: A cross-sectional study was conducted using a structured interviewer-administered survey between August and November 2019. Syrian refugee women who head their households and live outside camps were eligible. The survey included items investigating socio-demographic characteristics and conflict-related physical trauma history. The Refugee Health Screener-15 (RHS-15) scale was used to screen for emotional distress symptoms of depression, anxiety, and post-traumatic stress disorder (PTSD), with a score range of 0− 4 and higher scores indicating emotional distress. The Multidimensional Scale of Perceived Social Support (MSPSS) was utilized to assess the perceived support from family, friends, and significant others (score range 1− 7), with scores of 3− 5 and 5.1− 7.0 representing moderate and high support, respectively. The PTG Inventory (PTGI) scale investigated the positive transformation following trauma; the score range was 0− 5, and the cutoff point of ≥ 3 defined moderate-to-high growth levels.Results: Out of 140 invited refugee women, 95 were included, with a response rate of 67.9%. Their mean (SD) age was 41.30 (11.75) years, 50.5% were widowed, and 17.9% reported their husbands as missing persons. High levels of conflict-related traumatic exposure were found, including threats of personal death (94.7%), physical injury (92.6%), or both (92.6%); and a history of family member death (92.6%), missing (71.6%), or injury (53.7%). The mean (SD) RHS-15 score was above average (2.08 (0.46)), and most women (90.5%) were at high risk for depression, anxiety, and PTSD symptoms. The mean (SD) MSPSS score was 5.08 (0.71), representing moderate social support, with friends' support being the highest (5.23 (0.85)). The mean (SD) PTGI score was 2.44 (0.48), indicating low growth, with only 12.6% of women experiencing moderate-to-high growth levels. Spiritual change and personal strength had the highest sub-scores, with moderate-to-high growth levels experienced by 97.9% and 84.2%, respectively. Most women were more optimistic and religious, had feelings of self-reliance and better difficulties adapting, and were stronger than they thought. Statistically significant correlations of MSPSS and its subscales with RHS-15 and PTGI were detected.Conclusion: Significant but unspoken mental health problems were highly prevalent among Syrian refugee women and an imminent need for psychological support to overcome traumatic exposure. The role of social support seems to be prominent and needs further investigation.Keywords: refugee, women, Syrian, mental health, social support, trauma growth, Jordan, MSPSS, RHS-15, PTGI